Xenopus laevis 18S ribosomal RNA: experimental determination of secondary structural elements, and locations of methyl groups in the secondary structure model. - Atmadja, J (1984)
18S ribosomal RNA from X. laevis was subjected to partial digestion with ribonucleases A or T1 under a variety of conditions, and base-paired fragments were isolated. Sequence analysis of the fragments enabled five base-paired secondary structural elements of the 18S RNA to be established. Four of these elements (covering bases 221-256, 713-757, 1494-1555 and 1669-1779) confirm our previous secondary structure predictions, whereas the fifth (comprising bases 1103-1125) represents a phylogenetically conserved "switch" structure, which can also form in prokaryotic 16S RNA. The results are incorporated into a refined model of the 18S RNA secondary structure, which also includes the locations of the many methyl groups in X. laevis 18S RNA. In general the methyl groups occur in non-helical regions, at hairpin loop ends, or at helix boundaries and imperfections. One large cluster of 2'-O-methyl groups occurs in a region of complicated secondary structure in the 5'-one third of the molecule.